BONE HEALTH, MUSCLE STRENGTH AND LEAN MASS: RELATIONSHIPS AND EXERCISE RECOMMENDATIONS - Pimenta,Luciana Duarte (2019)
ABSTRACT Although muscle strength, lean mass and bone mineral content/density (BMC/BMD) are consistently reported as major outcomes of resistance training (RT), there is still no agreement on the RT regimen that is capable of achieving this result in men and women of different ages. This study describes the effects of RT on muscle strength, lean mass and bone mineralization, highlighting the relationships between them and analyzing the effectiveness of the RT protocol. Information searches were conducted in open access online academic libraries, using the BMC/BMD indices combined with muscle strength, body composition, and resistance exercises. The results showed changes in BMC/BMD in 72% of the studies published in the last decade. Among these, 77% recommended loads ≥ 80% 1-RM, 61% involved older individuals (> 60 years) and 61% had planning protocols of between 3 and 5 months (~12-20 weeks). The results also highlight muscle strength as a promising index of variations in BMC/BMD, with a moderate to high level of association (r2>0.5), which are specific for men and women in relation to the body region with best responsiveness. Among the studies published in last decade, about 61% had protocols involving only RT, and of these, 82% observed combined changes in BMC/BMD, body composition and muscle strength. This review therefore concludes that RT is important for improving muscle strength, increasing lean mass (whole-body and regional) and preventing risk factors that could impair the mineral integrity of the bone tissue, in individuals of all ages and sexes. Level of Evidence I; Systematic review of Level I RCTs (and study results were homogenous).